1999
DOI: 10.1046/j.1524-475x.1999.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase activity in keloids and hypertrophic scars

Abstract: Keloids and hypertrophic scars are characterized by excessive deposition of collagen, which may result from insufficient protein degradation. Little is known about the levels of two gelatinases, matrix metalloproteinase-2 (72 kD type IV collagenase) and matrix metalloproteinase-9 (matrix metalloproteinase-9; 92 kD type IV collagenase) in these abnormal scars. The purpose of this study was to determine levels of these proteinases in tissue from hypertrophic scars, keloids, and donor skin. Ten hypertrophic scar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 24 publications
3
59
1
4
Order By: Relevance
“…In our study, MMP-2 expression was consistent with the tissue repair process described by Neely et al [41], in which this MMP plays an active role in the constant remodelling of damaged tissue. In the HR and DRPGH groups, MMP-2 synthesis occurs early on, since at 3 days, the epidermis had completely closed and the dermis was of an organised structure.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, MMP-2 expression was consistent with the tissue repair process described by Neely et al [41], in which this MMP plays an active role in the constant remodelling of damaged tissue. In the HR and DRPGH groups, MMP-2 synthesis occurs early on, since at 3 days, the epidermis had completely closed and the dermis was of an organised structure.…”
Section: Discussionsupporting
confidence: 92%
“…In keloids, besides overproduction of dermal collagen and other fibroblast proteins, also disturbed ECM degradation is observed [11,19,20]. The FAP-α, a member of the group II integral serine proteases, may play an important role in remodeling of ECM and the invasive properties of keloids.…”
Section: Suzawa Et Al Revealed That Tranilast Selective Inhibition Omentioning
confidence: 99%
“…Poza nadprodukcją kolagenu i innych białek w keloidach obserwuje się również zaburzenia rozkładu ECM [11,19,20]. Białko FAP-α, zaliczane do grupy II integralnych proteaz serynowych, może odgrywać istotną rolę w przebudowie ECM oraz wpływać na właściwości inwazyjne keloidów.…”
Section: Suzawa Et Al Revealed That Tranilast Selective Inhibition Ounclassified
“…Previous reports exist on keloids and MMP. Neely et al reported that MMP-2 activity was significantly increased in hypertrophic scars and keloids (30). Oriente and co-workers reported that TGF-ß1 induces upregulation of MMPs in keloid fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%